Shifting of Adjective Shift in The News “Immanuel Kant: Warum Seine Philosophie So Aktuell Ist” - Avisena, Satrio; Niartanaya, Bagas; Rusmana, Ahmad (Universitas Negeri Malang, 2024)
This research examines the phenomenon of adjective shifts in the translation of news texts from German into Indonesian, focusing on the shifting of adjectives into different word classes in the target text. The case study is an article titled